Evaluation of monitoring youth exposure to alcohol advertising on cable television, United States 2016–19. - Ross, Craig S.; Henehan, Elizabeth R.; Alger, Charlotte; White, Laura F. (Addiction, 2021)
Background and aims: Exposure to alcohol advertising is associated with underage drinking, which contributes to adolescent morbidity and mortality. Alcohol advertisements are regulated by the alcohol industry. Our research team has published reports monitoring alcohol advertisers' compliance with industry guidelines. In this study, we estimated: (1) changes in youth and adult exposure to alcohol advertisements on cable television from 2016–19 and (2) changes in youth exposure to types of non‐compliant advertising highlighted in monitoring reports over the same period. Design Interrupted time–series analysis using data from Nielsen US national television audience estimates, 2012–19. Measures and methods: Outcome was advertising impressions (the total number of times an alcohol advertisement was viewed by youth or adults) by month. Non‐compliant exposure was impressions from advertisements that did not meet guidelines. Covariates were advertising spending in multiple media categories. Seasonal autoregressive integrated moving average models estimated trends in exposure before the publication of monitoring reports (2012–15 reference period) and during the monitoring period (2016–19). We compared the modeled exposure trend during the monitoring period to the reference period projected trend. Setting: United States. Participants: A total of 57 000 Nielsen panel households Findings Non‐compliant exposure declined 6158 [95% confidence interval (CI) = −11 406 to −911] million impressions, or −77.3% during the monitoring period compared with the reference period trend. Total youth exposure declined by 20 995 (CI = −34 701 to −7288) million impressions (27.0%). Non‐compliant exposure on programs, network dayparts and brands highlighted in monitoring reports declined by −82.4, −79.0 and −82.2%—more than other programs (−52.7%), network dayparts (−71.0%) or brands (143%). Adult exposure declined by 9.3%. Conclusions: Publication of alcohol advertising monitoring reports appears to have been associated with a 27.0% decline in US youth exposure to alcohol advertising on cable television and a 77.3% decline in US youth exposure to non‐compliant alcohol advertising.